2014
DOI: 10.1007/s12639-014-0501-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Plasmodium falciparum malaria parasites on haematological parameters in Ghanaian children

Abstract: Malaria is hyper-endemic in Ghana. Haematological alterations in the disease pathology may offer complimentary criteria to improve clinical and microscopy diagnosis. Our primary outcome was to evaluate haematological parameters in children with Plasmodium falciparum infections and report their predictive risk and diagnostic performance for malaria infections in Ghana. Haematological data, including thin and thick blood films were examined for children less than 12 years of age in a multicenter-based active cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 22 publications
2
12
1
Order By: Relevance
“…Previous study done in Ghana in patients below 20 years, reported that WBC and lymphocytes in malaria patients were lower compared to control subjects. The other leucocytes sub-types were not significantly different from control subjects [41]. However, the current study observed significantly high leucocytes and leucocytes sub-types derangements in malaria-SCD except neutrophils and basophils.…”
Section: Discussioncontrasting
confidence: 69%
“…Previous study done in Ghana in patients below 20 years, reported that WBC and lymphocytes in malaria patients were lower compared to control subjects. The other leucocytes sub-types were not significantly different from control subjects [41]. However, the current study observed significantly high leucocytes and leucocytes sub-types derangements in malaria-SCD except neutrophils and basophils.…”
Section: Discussioncontrasting
confidence: 69%
“…Full or complete blood count was conducted on each participant and there was a significant decrease in the haemoglobin concentration in the P. falciparum infected children compared to those not infected with malaria (Table 2 ). The mean haemoglobin concentration was 9.78 ± 2.4, giving credence to the fact that malaria-induced immune responses contributes to accelerated lysis of both parasitized and non-parasitized red cells which in turn results in the increased anaemia witnessed in P. falciparum infected children [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite many global studies reporting anemia, thrombocytopenia and leukopenia with malaria and typhoid in adults, limited studies of these cytopenias exist in Ghana. The studies in Ghana, are mostly on anemia in children [ 27 30 ] and in pregnant women [ 31 34 ]. Thus, this study was intended to determine the prevalence and association of cytopenias in adults with plasmodium or salmonella infections in Tamale.…”
Section: Introductionmentioning
confidence: 99%